SIMULASI SISTEM CARRIER SENSE MULTIPLE ACCESS WITH COLLISION DETECTION (CSMA/CD) LAN TIPE NON-PERSISTENT - Nirwana, Hafsah
Carrier Sense Multiple Access with Collision (CSMA/CD) with an ability to detect a collision is one of the most popular random access protocol. It is widely used in local area networks. A model of non persistent CSMA/CD is implemented in this research_ The model, capable of measuring the system's performance, represents the real system. Throughput value is used to measure the system's performance. Throughput is defined as the ratio of the average successful packet transmission time for a cycle to the total cycle time. The experiment uses some different values of several variables applied to the model simulation, such as, packet arrival rate, packet length, number of terminal, bit rate and length of transmission line. The results are compared with the calculation of the theoretical formulas. The comparison results are shown in the graphical diagrams.